207 Small molecule inhibitors of Sec61 cotranslational translocation regulate the phagocytosis checkpoint molecule CD47. (9th November 2020) - Whang, Jennifer; Fan, Andrea; Kirk, Christopher; Lowe, Eric; McMinn, Dustin; Millare, Beatriz; Rao, Meera
Abstract : Background: Many tumor cells escape immune cell clearance by overexpressing CD47, a multi-pass transmembrane protein, which binds signal regulatory protein α (SIRPα) on macrophages leading to decreased phagocytic activity. Blockade of CD47/SIRPα interactions enhances macrophage phagocytosis and is being targeted with antibody-based drugs, some of which are used in combination therapies in clinical trials. A novel method to target CD47 is through the inhibition of cotranslational translocation of transmembrane proteins. Immediately after exiting the ribosome, signal sequences that are unique to each protein are directed through the Sec61 channel into the ER for extracellular expression. 1 Several Sec61-targeting compounds have been identified to suppress translocation in a signal sequence-specific manner. 2 We previously described Sec61 inhibitors capable of selectively targeting immune checkpoint proteins and enhancing T cell function. 3 Here, we demonstrate the blockade of CD47 expression on tumor cells and enhancement of macrophage phagocytosis with small molecule inhibitors of Sec61. Methods: Sec61-dependent expression of target proteins was assayed using HEK293 cells overexpressing constructs comprised of signal sequences fused to a luciferase reporter. Stimulated PBMCs or tumor cells were incubated with Sec61 inhibitors, and surface expression of checkpoint molecules were examined by flow cytometry. Necrotic and apoptotic cells were assessed by Annexin V and 7AAD labeling. Human CD14+ monocytes were differentiated to M1- or M2-type macrophages. Jurkat or SKBR3 cells were incubated with Sec61 inhibitors, labeled with a pH sensitive dye and co-cultured with macrophages to assess phagocytosis. Results: We identified Sec61 inhibitors that block select immune checkpoint proteins. Compounds demonstrated either selective or multi-target profiles in transient transfection screens, which was supported by decreased protein expression on activated T cells. KZR-9275 targeted multiple checkpoint molecules, including PD-1, LAG-3 and CD73, along with a potent inhibition of the CD47 signal sequence reporter. CD47 surface expression was decreased on Jurkat and SKBR3 cells following 72 hours of compound treatment. KZR-9275 treatment of SKBR3 cells induced a minor increase in apoptotic cells, which was not detected in Jurkat cells. Increased macrophage phagocytosis, especially with M2-type macrophages, was observed when Jurkat or SKBR3 cells were pre-treated with KZR-9275. Conclusions: Our findings demonstrate that Sec61 inhibitors can block the expression of CD47, a phagocytosis checkpoint protein, on tumor cells and subsequently modulate macrophage phagocytic activity. Small molecule inhibitors of Sec61 provide an opportunity to target multiple checkpoint proteins on various cell populations. Future in vivo tumor models will assess the efficacy of Sec61 inhibitors to provide combination-like therapy. References: Park E, Rapoport TA. Mechanisms of Sec61/SecY-mediated protein translocation across membranes. Annu Rev Biophys 2012; 41 :1–20. Van Puyenbroeck V, Vermeire K. Inhibitors of protein translocation across membranes of the secretory pathway: novel antimicrobial and anticancer agents. Cell Mol Life Sci 2018; 75 :1541–1558. Whang J, Anderl J, Fan A, Kirk C, Lowe E, McMinn D, et al. Targeting multiple immune checkpoint proteins with novel small molecule inhibitors of Sec61-dependent cotranslational translocation. 34th Annual Meeting & Pre-Conference Programs of the Society for Immunotherapy of Cancer (SITC 2019): part 2. J Immunother Cancer 2019; 7: 283. Abstract 815.